2016
DOI: 10.22159/ijpps.2016v8i10.13673
|View full text |Cite
|
Sign up to set email alerts
|

SYNTHESIS AND ANTI-MICROBIAL ACTIVITY OF 1-(6-NITRO-2H-BENZO[b][1,4]THIAZINE-3(4H)-YLIDENE)HYDRAZINE-1,1-DIOXIDE DERIVATIVES

Abstract: <p><strong>Objective: </strong>The objective of this research was to synthesize and evaluate anti-microbial properties of 1-(6-nitro-2<em>H</em>-benzo[<em>b</em>][1,4]thiazine-3(4<em>H</em>)-ylidene)hydrazine-1,1-dioxide derivatives.</p><p><strong>Methods: </strong>These new compounds were synthesized by reaction of 2<em>H</em>-benzo[b][1,4]thiazin-3(4<em>H</em>)-one with hydrazine derivatives and oxidized at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
(11 reference statements)
0
2
0
Order By: Relevance
“…Literature [32][33][34][35][36][37][38][39] revels that thiazines based heterocycles are treated as major group of heterocycles. On the basis of above data, it has been confirmed that a variety of thiazine based heterocycles are believed as probable antimicrobial agents.…”
Section: Resultsmentioning
confidence: 99%
“…Literature [32][33][34][35][36][37][38][39] revels that thiazines based heterocycles are treated as major group of heterocycles. On the basis of above data, it has been confirmed that a variety of thiazine based heterocycles are believed as probable antimicrobial agents.…”
Section: Resultsmentioning
confidence: 99%
“…Substituted thiazines ring-based chemical compounds are considered as organic compounds holding four carbon atoms and one N and S atom at various place in the rings containing six members present in various structures. Further, a variety of organic compounds are synthesized by the use of 1, 3 and 1,4 thiazines [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%